OPTIMIZATION OF APPLE COMMODITY DISTRIBUTORS IN THE SUPPLY CHAIN USING THE ANALYTICAL HIERARCY PROCESS (AHP) METHOD IN THE NONGKOJAJAR APPLE JUICE SME - hanif fauzi (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2023)
Sari Apel small and medium enterprises Nongkojajar is one of the companies that produces apples. In order for the advanced company and develop it well, proper planning is needed in determining the amount of apple supply by selecting the supplier and determining the number of apples supply for the company that will lead to the amount of production and sale of apple cider that uses apples to get optimal profit through the supply of main raw materials to fulfill consumer demand with the Analytical Hierarchy Process method. The theory used in this research is the selection of optimal suppliers which is analyzed using the Analytical Hierarchy method. The steps used to solve the problem by determining the supplier criteria and the optimal amount of apple supply. Data collection of this research is obtained from the direct observation using Analytical Hierarchy Process. The steps that need to be done in this research are supplier data and the number of supply data. In order to solve this problem, the researcher used Analytical Hierarchy Process method assisted by expert choice software.